"Lighten This Burden of Ours": Acceptability and Preferences Regarding Injectable Antiretroviral Treatment Among Adults and Youth Living With HIV in Coastal Kenya. (8th March 2021) - Simoni, Jane M.; Beima-Sofie, Kristin; Wanje, George; Mohamed, Zahra H.; Tapia, Kenneth; McClelland, R. Scott; Ho, Rodney J. Y.; Collier, Ann C.; Graham, Susan M.
Background: Long-acting injectable (LAI) antiretroviral therapy (ART) may offer persons living with HIV (PLWH) an attractive alternative to pill-based treatment options, yet acceptability data remain scant, especially in sub-Saharan Africa. Methods: We conducted 6 focus group discussions with PLWH, including key stake holder groups, and analyzed data with content analysis. Results: Initial reactions to the idea of LAI-ART were often positive. The primary advantages voiced were potential to facilitate improved adherence and alleviate the burden of daily pill-taking while avoiding inadvertent disclosure and HIV stigma. Potential side effects were a particular concern of the women. Most participants preferred clinic-based administration over self-injections at home due to concerns about safety, privacy, and potential need for refrigeration. Conclusions: LAI-ART may be acceptable in Kenya, provided injections are infrequent and delivered in a clinic setting. However, HIV stigma, fear of potential side effects, and limited clinical capacity would need to be addressed.